Association between synovial fluid prostanoid levels and ultrasonographic findings in knee osteoarthritis - Gülsev Özen; Demirhan Dıraçoğlu; Ekin İlke Şen; Zeynep Çelik; Tuğba Şahbaz; Gökçe Topal (Cukurova Medical Journal, 2021)
Purpose. The aim of this study was to investigate the association between prostanoid [thromboxane (TxA2) and prostacyclin (PGI2)] levels in synovial fluid and infrapatellar fat pad (IPFP)/ suprapatellar fat pad (SPFP) thickness as well as other clinical findings in knee steoarthritis (OA) patients. Materials and Methods: 16 patients with knee OA with effusion were included. The average pain levels were evaluated using a Visual Analogue Scale (VAS). The pain, stiffness, and physical functions were evaluated using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). The levels of 6-keto-PGF1α, stable metabolite of PGI2, and TxB2, stable metabolite of TxA2, were measured in synovial fluid using an enzyme immunoassay. Results: 6-keto-PGF1α levels were significantly greater than TxB2 levels in synovial fluid of patients with OA. TxB2 levels and TxB2/6-keto- PGF1α ratio were negatively correlated with SPFP and cartilage thickness, respectively. IPFP thickness was positively correlated with SPFP thickness and effusion volume. WOMAC scores were positively correlated with VAS-activity and VAC-evening scores. Conclusion: In comparison to 6-keto- PGF1α levels in synovial fluid, TxB2 levels seem to be more associated with ultrasonographic findings in patients with OA.